Transplanting as an option to cope with abiotic stress in high-altitude lowland rice production systems in East Africa - Abera, B.B.; Senthilkumar, Kalimuthu; Cotter, M.; Asch, F. (Wiley, 2022)
The current practice of direct seeding in East‐African high‐altitude rice farming systems is constrained by water availability early in the season and low temperatures later in the season at the crop's critical reproductive stage. Thus, productivity is restricted as only short‐duration varieties can be grown due to the risk of crop failure. To fully exploit the yield potential of such rainfed systems, the best combination of crop establishment methods and climatic ‘best fit’ genotypes is required. In this study, nine rice genotypes were evaluated under direct seeding and transplanting in the 2016 and 2017 cropping seasons with the aim of identifying genotype by environment by management combinations best fitting the high‐altitude, rainfed rice production systems. On average across all genotypes, transplanting had a positive yield effect of 18% in 2016 and 23% in 2017. Regarding the phenological development, individual phenophases were not significantly affected by transplanting relative to direct seeding; however, vegetative development stages in transplanted rice tended to be about 15% longer than when direct seeded. Even though transplanting led to extended vegetative growth, the time in the nursery allowed the plants to escape the cold spell late in the season. The results from the current study provide options to adapt cropping calendars by combining genetic resources with targeted crop management, thus improving and stabilizing yields of rainfed lowland rice farming systems at high altitude.